2006
DOI: 10.1038/sj.bjc.6603374
|View full text |Cite
|
Sign up to set email alerts
|

The role of socio-economic status in the decision making on diagnosis and treatment of oesophageal cancer in The Netherlands

Abstract: In the United States (USA), a correlation has been demonstrated between socio-economic status (SES) of patients on the one hand, and tumour histology, stage of the disease and treatment modality of various cancer types on the other hand. It is unknown whether such correlations are also involved in patients with oesophageal cancer in The Netherlands. Between 1994 and 2003, 888 oesophageal cancer patients were included in a prospective database with findings on the diagnostic work-up and treatment of oesophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…7,8 Pancreatic cancer patients with a low SES were found to be less likely to undergo surgical treatment. 7 In patients with EC, it was reported that high-SES patients underwent esophagectomy more frequently, compared with low-SES patients.…”
mentioning
confidence: 97%
“…7,8 Pancreatic cancer patients with a low SES were found to be less likely to undergo surgical treatment. 7 In patients with EC, it was reported that high-SES patients underwent esophagectomy more frequently, compared with low-SES patients.…”
mentioning
confidence: 97%
“…In the United States, African-American patients with oesophageal cancer were less likely to undergo surgical resection compared to Caucasian patients [62][63][64] . In the Netherlands, low socio-economic status proved to be associated with a lower chance of resection 65 . These disparities are not fully explained by differences in medical factors 64 .…”
Section: Patient Selectionmentioning
confidence: 99%
“…These disparities are not fully explained by differences in medical factors 64 . It has been suggested that patients' but possibly also physicians' preferences might differ among different socio-economic groups of patients 65 .…”
Section: Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Previous work has identified the importance of patient and physician characteristics with respect to treatment and clinical management. 46,47 For example, patients with lower SES have been shown to be perceived as less attractive by physicians, which may influence the inequities observed in consultation times, 48 referral patterns, and overall medical management. 49 Additionally, women who are more marginalized are less likely to be assertive and be strong advocates for their medical management.…”
Section: Discussionmentioning
confidence: 99%